The influence of Abraham Cohen de Herrera's kabbalah on Spinoza's metaphysics - Beltrán, M. (The Iberian Religious World, 2016)
In this book the author seeks to find historiographical and textual evidence that Abraham Cohen de Herrera 's main kabbalistic work, Puerta del Cielo , influenced Spinoza's metaphysics as it is expounded in his later work, the Ethica . Many of the most important ontological topics maintained by the philosopher, like the concept of the first cause as substance, the procession of the infinite modes, the subjective or metaphorical reality of the attributes, and the two different understandings of God, were anticipated in Herrera's mystical treatise. Both shared a particular consideration of panentheism that entails acosmism. This influence is proven through a comparative examination of the writings of both authors, as well as a detailed research on previous Jewish philosophical thought.